From core collapse to superluminous: the rates of massive stellar explosions from the Palomar Transient Factory. Issue 4 (21st November 2020) - Frohmaier, C; Angus, C R; Vincenzi, M; Sullivan, M; Smith, M; Nugent, P E; Cenko, S B; Gal-Yam, A; Kulkarni, S R; Law, N M; Quimby, R M
ABSTRACT: We present measurements of the local core-collapse supernova (CCSN) rate using SN discoveries from the Palomar Transient Factory (PTF). We use a Monte Carlo simulation of hundreds of millions of SN light-curve realizations coupled with the detailed PTF survey detection efficiencies to forward model the SN rates in PTF. Using a sample of 86 CCSNe, including 26 stripped-envelope SNe (SESNe), we show that the overall CCSN volumetric rate is r^CC_v=9.10_-1.27^+1.56× 10^-5 SNe yr^-1 Mpc^-3 h_70^3 at 〈 z 〉 = 0.028, and the SESN volumetric rate is r^SE_v=2.41_-0.64^+0.81× 10^-5 SNe yr^-1 Mpc^-3 h_70^3 . We further measure a volumetric rate for hydrogen-free superluminous SNe (SLSNe-I) using eight events at z ≤ 0.2 of r^SLSN-I_v=35_-13^+25 SNe yr^-1Gpc^-3 h_70^3, which represents the most precise SLSN-I rate measurement to date. Using a simple cosmic star formation history to adjust these volumetric rate measurements to the same redshift, we measure a local ratio of SLSN-I to SESN of 1/810^+1500_-94, and of SLSN-I to all CCSN types of 1/3500^+2800_-720 . However, using host galaxy stellar mass as a proxy for metallicity, we also show that this ratio is strongly metallicity dependent: in low-mass (log M * < 9.5 M⊙ ) galaxies, which are the only environments that host SLSN-I in our sample, we measure an SLSN-I to SESN fraction of 1/300^+380_-170 and 1/1700^+1800_-720 for all CCSN. We further investigate the SN rates a function of host galaxy stellar mass, and show that the specific rates of all CCSNe decrease with increasing stellar mass.